Lycorine suppresses the malignancy of breast carcinoma by modulating epithelial mesenchymal transition and β-catenin signaling - Yanfang, Sun; Gu, Yi; Gao, Xiaoyan; Jin, Xiaoyan; Wink, Michael; Sharopov, Farukh S.; Yang, Linjun; Sethi, Gautam (Pharmacological research, 2023)
Lycorine, an isoquinoline alkaloid can exhibit significant anti-cancer effects. The present study was conducted to illustrate the underlying mechanisms of action of lycorine on breast carcinoma under in vitro and in vivo settings Tandem Mass Tag assay and Kyoto Encyclopedia of Genes and Genomes analysis revealed that 20 signaling pathways were closely related to tumorigenesis, especially Wnt signaling pathway and tight junctions. The results demonstrated that lycorine evidently inhibited the proliferation of MDA-MB-231 and MCF-7 cells with IC50 values of 1.84 ± 0.21 μM and 7.76 ± 1.16 μM, respectively. It also blocked cell cycle in G2/M phase, caused a decrease in mitochondrial membrane potential, and induced apoptosis pathways through regulating caspase-3, caspase-8, caspase-9, and PARP expression. Moreover, lycorine effectively repressed the β-catenin signaling and reversed epithelial-mesenchymal transition (EMT) process. Furthermore, 4T1/Luc homograft tumor model was used to further demonstrate that lycorine significantly inhibited the growth and metastasis of breast tumor. These findings highlight the significance of lycorine as potential anti-neoplastic agent to combat breast cancer.